Rate and Predictors of Hesitancy toward SARS-CoV-2 Vaccine among Type 2 Diabetic Patients: Results from an Italian Survey - Federica Guaraldi; Marco Montalti; Zeno Di Valerio; Edoardo Mannucci; Besmir Nreu; Matteo Monami; Davide Gori (Vaccines, 2021)
Vaccine hesitancy (VH) has been identified as one of the major health concerns of our time by the World Health Organization. It may prove especially detrimental in the light of the ongoing SARS-CoV-2 pandemic, as vaccination campaigns still represent the primary strategy against the detrimental consequences of the pandemic. Among patients suffering from type 2 diabetes mellitus (DB), who are particularly vulnerable to COVID-19, VH might represent an even more serious threat. Therefore, our study focuses on identifying potential determinants of VH among patients with type 2 diabetes. Study participants (n = 1176) filled in a two-section online self-administered questionnaire, answering questions regarding demographic and anamnestic data, as well as their intention to accept any vaccination against COVID-19. Some possible reasons underlying VH were investigated as well. An overall hesitancy rate of 14.2% was registered. Data showed how older age, male gender, higher education level, and having been vaccinated for seasonal influenza in 2020–2021 were associated with a significantly higher propensity to receive the COVID-19 vaccine. On the contrary, having experienced adverse effects following past vaccinations was a negative predictor. In addition to confirming an array of predictors of VH, we found a worryingly high prevalence of VH among diabetics, who have been shown to be particularly exposed to severe COVID-19 and death. These findings may be useful in planning targeted action toward acceptance improvement and enhancing the efficacy of vaccination campaigns.